Real-Time Temperature Monitoring in an Optical Trap - Cordero-Carrasco, R (IEEE-INST ELECTRICAL ELECTRONICS ENGINEERS INC, 2022)
This work demonstrates, for the first time to our knowledge, that it is possible to measure the temperature of an optical trap (OT) using an optical fiber sensor tip. A polymer capped fiber optic Fabry-Perot interferometer, which is structure and temperature sensing characteristics have been well studied, was used. The surface of the polymer cavity, attached to the single-mode fiber tip immersed in Phosphate Buffered Saline, was placed in the optical trap. A temperature change of 1.63 +/- 0.021 degrees C was measured when the power of the laser, emitting at 975nm, was increased by 100 mW. The proposed setup facilitates the measurement of temperature, since it does not require the use of fluorescent dyes and it even works while having a captured particle; these advantages allow it to be included in any OT system.